The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.26500/jarssh-06-2021-0202
|View full text |Cite
|
Sign up to set email alerts
|

Information seeking behavior among public library users: Understanding nature of information searching

Abstract: Aim: The behavior of information seeking is the product of the need perceived by the information user, who makes demands for either formal or non-formal information sources or services, leading to attainment or failure. People look for information and use it to fulfill their assigned task while they engage in information finding activity. As an information providing agency, the mandate of the public library is to meet the needs of the public for information. The primary goal of the public library is therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…While 17.5% were not satisfied as the existing information services were perceived to be less effective and efficient. This is in agreement with the findings of Athukorala et al, which indicated that majority of the sample surveyed were not satisfied with the library's professional information [6]. Thus, this further support the point that existing information services and systems at center used by respondents were in one way or the other met and satisfied their information needs and improvement need to be made to fully satisfy the users' need.…”
Section: Level Of Satisfaction To the Existing Information Servicessupporting
confidence: 91%
See 1 more Smart Citation
“…While 17.5% were not satisfied as the existing information services were perceived to be less effective and efficient. This is in agreement with the findings of Athukorala et al, which indicated that majority of the sample surveyed were not satisfied with the library's professional information [6]. Thus, this further support the point that existing information services and systems at center used by respondents were in one way or the other met and satisfied their information needs and improvement need to be made to fully satisfy the users' need.…”
Section: Level Of Satisfaction To the Existing Information Servicessupporting
confidence: 91%
“…This implies that the libraries in the two centers need to be improved and provide relevant sources. Describing the importance of library visit, Athukorala et al, brought forward that libraries are often viewed as information market place [6].…”
Section: Frequency To Visit Center Librarymentioning
confidence: 99%